Pathophysiology of metalloproteinase matrix in relation to morbid obesity and associated pathologies - Mirica, Radu Mihail; Ionescu, Mihai; Mırıca, Alexandra; Gınghına, Octav; Iosıfescu, Razvan; Vacarasu, Andrei- Bogdan; Cıotarla, Danut- Constantin; Rosca, Adrian; Zagrean, Leon; Iordache, Niculae (The European Research Journal, 2022)
Matrix Metalloproteinases (MMPs), these calcium-dependent zinc-containing endopeptidases play an important role in adipogenesis and angiogenesis by modifying tissues and degrading the extracellular matrix (ECM). Matrix glycoproteins, gelatin, collagens, proteoglycans and elastin are all found in the ECM. Current meta-analysis confirmed the lower levels of IL-6 and CRP was found following bariatric surgery. Several studies have shown correlations between E-selectin levels, BMI, and MMP-9 levels. There was also a strong link between the metalloproteinases MMP-2 and MMP-9. MMP-2 and adiponectin levels are related. MMP-9 levels, on the other hand, were modestly linked with E-selectin and HDL cholesterol levels, as previously stated. Also current observations imply that alterations in the ECM caused by MMP-mediated degradation may be crucial for the differentiation of adipocytes. The most crucial component of this is that MMPs are involved in the remodeling of tissue after gastric bypass surgery, as revealed by these markers (especially MMP-2 and MMP-9). Thus, it is tempting to assume that adipocyte derived MMPs may constitute a novel pharmaceutical target for limiting adipose tissue development through the reduction of adipocyte differentiation and angiogenesis. MMP-2 exhibits far more accurate oscillations than MMP-9 during pre- and post-surgical weight fluctuations, and hence may be used as a predictor for gastric bypass success. The purpose of this paper is to conduct a comprehensive review of the literature with an emphasis on the critical functions that MMPs have in the pathophysiology of obesity and the related diseases.